Manejo del paciente odontológico durante el periodo de la pandemia SARS-COV-2 (COVID-19): Revisión sistemática de la literatura - Cuenca Cuevas, Valentina; Tovar Ibarra, Paula Camila; Rodríguez, Ana Valentina (Universidad Antonio Nariño, 2021)
The SARS-CoV-2 (Covid-19) virus health crisis has been defined as a worldwide problem that to date has no cure and various protocols of control and biosafety measures for dental care during the pandemic due to covid-19, where it is intended to protect the service provider, support and the patient. At the international level, the ministry of health and social protection in the management process of interventions for health promotion and disease prevention in view of the need to develop and reinforce biosecurity plans in order to mitigate and avoid the number of infections, issues decree 539 of 2020 where the document is located “Biosafety guideline for the provision of services related to the care of the oral health during the period of the SARS-CoV-2 (COVID-19) pandemic ” Our degree work will focus on knowing the protocols for handling dentistry during the SARS-CoV-2 (covid 19) pandemic based on the systematic review of articles obtained in different databases. Thus, the present work will allow the execution safe dental care by students and professionals who specialize in clinical practices, taking into account the recommendations or guidelines found in based on scientific evidence to have a clinical-scientific knowledge during practice.